2009
DOI: 10.1161/circresaha.109.199984
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin Stimulates Smooth Muscle Cell Differentiation From Peripheral Blood Mononuclear Cells via Protease-Activated Receptor-1, RhoA, and Myocardin

Abstract: Rationale: Smooth muscle precursor cells have previously been reported to reside in bone marrow and in the circulation, but little is currently known regarding the proximate stimuli for smooth muscle cell differentiation of these putative progenitors. Objective: Because local thrombin generation occurs as an initial response to vascular injury, we hypothesized that thrombin may influence the differentiation of circulating smooth muscle progenitor cells. Methods and Results: Peripheral blood mononuclear cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 14 publications
3
44
0
Order By: Relevance
“…Another potential confounder is the expression of SM α-actin by myeloid lineage cells. Although it has been shown that cultured macrophages can express SMC markers, including SM α-actin after stimulation with transforming growth factor-β or thrombin, 30,31 to our knowledge there is no evidence for SM α-actin expression by myeloid lineage cells in human or mouse tissues in vivo. 21,22,32 There is, however, the likelihood that we have not identified all of the SMCs involved in intimal foam cell formation.…”
Section: Discussionmentioning
confidence: 84%
“…Another potential confounder is the expression of SM α-actin by myeloid lineage cells. Although it has been shown that cultured macrophages can express SMC markers, including SM α-actin after stimulation with transforming growth factor-β or thrombin, 30,31 to our knowledge there is no evidence for SM α-actin expression by myeloid lineage cells in human or mouse tissues in vivo. 21,22,32 There is, however, the likelihood that we have not identified all of the SMCs involved in intimal foam cell formation.…”
Section: Discussionmentioning
confidence: 84%
“…recently to be a thrombin-promoted action. 19 TF and FVII, FX, FXI, and FXII were either weakly or focally present on macrophages, and FXII was also found on some foam cells. FIX showed a pronounced focal distribution on both macrophages and foam cells.…”
Section: Immunohistochemical Staining: Saalmentioning
confidence: 94%
“…Initially, peripheral blood-derived or bone marrow-derived mononuclear cells (MNCs) were transplanted as endothelial progenitor cells, which should be incorporated into newly formed vessels. However, an increasing number of reports indicate that transplanted MNCs augment angiogenesis by functioning as angiogenic factorproducing cells, 4,5 progenitors of mural cells, 6,7 or cells that stimulate muscle cells to produce angiogenic factors. 8 Unselected MNCs, rather than MNCs enriched for CD34, CD133, or vascular endothelial growth factor receptors, have been preferentially used for cell therapy.…”
Section: See Accompanying Article On Page 1277mentioning
confidence: 99%